2021
DOI: 10.1038/s41598-021-88363-9
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional signatures in prefrontal cortex confer vulnerability versus resilience to food and cocaine addiction-like behavior

Abstract: Addiction is a chronic relapsing brain disease characterized by compulsive reward-seeking despite harmful consequences. The mechanisms underlying addiction are orchestrated by transcriptional reprogramming in the reward system of vulnerable subjects. This study aims at revealing gene expression alterations across different types of addiction. We analyzed publicly available transcriptome datasets of the prefrontal cortex (PFC) from a palatable food and a cocaine addiction study. We found 56 common genes upregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 59 publications
0
18
1
Order By: Relevance
“…Genes coding for the adenosine A2A receptor (Adora2a; FC: 2.531), dopamine receptor D2 (Drd2; FC: 1.843), G protein subunit gamma 7 (Gng7; FC: 1.389), and protein phosphatase 1 regulatory inhibitor subunit 1B (Ppp1r1b; FC: 1.356) were the most interconnected nodes each with edges reaching to five other genes in the network. In contrast to the current findings, a separate study found Adora2a, Drd2, and Ppp1r1b to be increased in the mPFC of "vulnerable" mice that exhibit heightened cocaine-motivated behavior, relative to "resilient" mice; phenotypes were assigned to each animal through multi-factor analysis of operant behavior observed during cocaine self-administration sessions (e.g., cocaine intake) (Navandar et al, 2021). While both studies implicate these genes to be important regulators of cocaine-motivated behaviors, differential gene expression patterns could be expected to be dependent on the given stage of CUD being modeled (active drug consumption vs. abstinence).…”
Section: Figurecontrasting
confidence: 99%
“…Genes coding for the adenosine A2A receptor (Adora2a; FC: 2.531), dopamine receptor D2 (Drd2; FC: 1.843), G protein subunit gamma 7 (Gng7; FC: 1.389), and protein phosphatase 1 regulatory inhibitor subunit 1B (Ppp1r1b; FC: 1.356) were the most interconnected nodes each with edges reaching to five other genes in the network. In contrast to the current findings, a separate study found Adora2a, Drd2, and Ppp1r1b to be increased in the mPFC of "vulnerable" mice that exhibit heightened cocaine-motivated behavior, relative to "resilient" mice; phenotypes were assigned to each animal through multi-factor analysis of operant behavior observed during cocaine self-administration sessions (e.g., cocaine intake) (Navandar et al, 2021). While both studies implicate these genes to be important regulators of cocaine-motivated behaviors, differential gene expression patterns could be expected to be dependent on the given stage of CUD being modeled (active drug consumption vs. abstinence).…”
Section: Figurecontrasting
confidence: 99%
“…DRD1 is found in the postsynaptic membrane where it regulates the postsynaptic transmission of dopamine. It is expressed in excitatory neurons in the prefrontal cortex ( Navandar et al, 2021 ). It is a G-protein coupled receptor (GPCR) that activates adenylyl cyclase after dopamine binds to it ( Undieh, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although the functional role of each subtype remains to be investigated, this suggests that certain Drd1 -expressing neuronal subtypes in the PFC may be more involved in the process of cocaine addiction than others ( Bhattacherjee et al, 2019 ). Further analysis on dataset of cocaine-addicted mice revealed that Drd1 and Drd2 genes are both upregulated in cocaine addiction and are almost solely expressed in excitatory neurons, with Drd1 also being found at lower levels in inhibitory neurons, oligodendrocyte and endothelial cells in the mPFC ( Bhattacherjee et al, 2019 ; Navandar et al, 2021 ).…”
Section: Dopamine Release and Dopamine Receptors In The Developing Prefrontal Cortexmentioning
confidence: 99%